Level Up! : En konceptutveckling som exemplifieras på festivalen Piteå Dansar och Ler med fokus på implementering av teorier från gamification och upplevelsebaserade modeller - Sannebjörk, Linn (2016)
The development of the society has gone from customers buying products, to consuming guest experiences. This study was conducted to find out how the experience production can be combined with the increasing global trend of gamification, to contribute to research whether it is possible to create a meaningful experience through a composition of these two areas. Festivals in Sweden has become an increasingly interesting area of scientific research. A case study is performed at the festival Piteå Dansar och Ler by utilizing a semi-structured interview, concept development and reviewed literature, a theoretical concept is developed and exemplified at the festival. The concept consist of a mobile application that provides game mechanics, and experiences based on the human senses where guests can participate actively without technology. The results shows that there are good opportunities to combine theories of gamification with experience-based models that can bring a wide spectrum of experience, physical and digital activities. A concluding discussion about the importance of further developing the concept and to test it empirically to see whether the concept is user-friendly are suggested.Key words: Experience production, gamification, festivals, concept development. Validerat; 20160620 (global_studentproject_submitter)